2019
DOI: 10.31616/asj.2018.0215
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Fat-Derived Mesenchymal Stem Cell: First Report of Epidural Fat-Derived Mesenchymal Stem Cell

Abstract: Study Design Experimental study. Purpose To determine whether epidural fat (EF) tissue contains mesenchymal stem cells (MSC). Overview of Literature Spine surgeons are unaware of the contents of EF tissue and the reason for its presence between the ligamentum flavum and the dura mater; therefore, EF tissues are routinely eliminated during surgical procedures. However, EF removal causes certain postoperative problems, such as post-laminectomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…From an experimental study, we found the existence of MSC within the epidural fat, and we called that as EF-MSC, the outcome of which was published at an international peer-reviewed journal. 26 Moreover, we confirmed that EF-MSC differed markedly from MSC from other fat tissues, in terms of cell isolation and proliferation, characterization, differentiation potential, and especially expression of neuronal markers and neurogenic differentiation, results of which will be presented soon.…”
Section: Discussionsupporting
confidence: 69%
“…From an experimental study, we found the existence of MSC within the epidural fat, and we called that as EF-MSC, the outcome of which was published at an international peer-reviewed journal. 26 Moreover, we confirmed that EF-MSC differed markedly from MSC from other fat tissues, in terms of cell isolation and proliferation, characterization, differentiation potential, and especially expression of neuronal markers and neurogenic differentiation, results of which will be presented soon.…”
Section: Discussionsupporting
confidence: 69%
“…As the number of passages increases, the morphology of the hMSCs becomes more bipolar and VEGF expression decreases compared to that in the low passage number hMSCs [26,27]. Figure 3A shows that high passage number hMSCs (P12) were bipolar and more elongated as compared to the low passage number hMSCs (P6).…”
Section: Resultsmentioning
confidence: 99%
“…These include inflammatory diseases, and related studies have been continuously reported [ 10 ]. MSCs can be isolated from diverse tissues, such as umbilical cord blood, bone marrow, muscle, and adipose tissue [ 10 , 11 , 12 ]. In particular, various studies have been reported on the characteristics and therapeutic effects of adipose tissue-derived MSCs [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, various studies have been reported on the characteristics and therapeutic effects of adipose tissue-derived MSCs [ 13 , 14 , 15 ]. MSCs have also been isolated from epidural adipose tissue with reports of therapeutic effects [ 11 , 16 ]. Although MSCs have a variety of effects on tissue repair and meaningful therapeutic effects in the treatment of various diseases, due to several limitations of MSCs, new therapeutic strategies are required to treat additional disease and cells, [ 17 ].…”
Section: Introductionmentioning
confidence: 99%